UJI TOKSISITAS AKUT EKSTRAK ETANOL DAUN CENGKEH (Syzygium Aromaticum) TERHADAP LARVA ARTEMIA SALINA L. DENGAN METODE BRINE SHRIMP LETHALITY TEST (BSLT) - Adhisty Kharisma Justicia; Riris Sagita Ardianti (Jurnal Komunitas Farmasi Nasional, 2021)
Clove (Syzygium aromaticum) is a spice plant found on Lemukutan Island, Bengkayang, West Kalimantan. Clove leaves (Syzygium aromaticum) belong to the Myrtaceae tribe which contains secondary metabolites, namely flavonoids and saponins, which are potentially toxic. This study aims to determine whether the ethanol extract of clove leaves (Syzygium aromaticum) has toxic properties against Artemia salina Leach larvae and to know its value. Test animals used in this study were Artemia Salina Leach Larvae using BSLT method. Tests were carried out with different concentrations of 1000 μg/mL, 750 μg/mL, 500 μg/mL, 250 μg/mL, 100 μg/mL and 0 μg/mL, each group consisting of 10 larvae tails with replication 5 times and 1x24 hour observation time. The results obtained were then analyzed using the probit method using Ms. Excel. The results showed that clove leaves (Syzygium aromaticum) had toxic effects on Artemia salina Leach larvae and the value obtained was 71.9448 µg/ml.